Impact of Food Systems Transformation on Dietary Patterns and Public Health in Africa: A Mini Review - (:unkn) unknown (My University, 2024)
Background: The African food system has undergone significant transformations due to globalization, urbanization, economic development, and policy changes. However, agricultural productivity has been constrained by climate variability, limited technology, and inadequate infrastructure. This study aims to present the current state of evidence on how shifts in Africa’s food system affect dietary intake and health outcomes.Methodology: A comprehensive literature search was conducted using databases such as PubMed, Web of Science, Scopus, and Google Scholar. Keywords included “food systems transformation,” “dietary patterns,” “public health,” “nutrition transition,” and “Africa”. Seven (7) studies published in English from 2010 to 2023 were selected based on their relevance. Studies included assessed the impact of food system changes on diet and health across four African regions. Data extraction was performed independently by three reviewers to ensure accuracy and a narrative synthesis approach was used to integrate findings from the selected studies.Results: The review identified that urbanization and economic development have shifted African diets from traditional, nutrient-rich foods to processed foods high in sugars and unhealthy fats. Trade liberalization has increased access to energy-dense, nutritionally poor foods, raising obesity and non-communicable disease rates. Supermarket expansion and adoption of modern food processing techniques have driven preferences for convenience foods and animal products, causing dietary imbalances and a double burden of malnutrition. Climate change and political instability exacerbate food insecurity, particularly among women and children, further increasing vulnerability to infectious diseases and straining healthcare systems.Conclusion: Current changes in Africa's food system have significantly impacted dietary patterns and public health, resulting in increased healthcare expenditure and a gr
Keywords: African Research